Latency of prosaccades and antisaccades in professional shooters - Morollo, M.; Di Russo, F.; Pitzalis, S.; Spinelli, D. (Medicine & Science in Sports & Exercise, 2006)
Purpose: This study evaluated hypothesis that the faster saccadic reaction time in professional clay-target shooters found in a previous study was because of a superiority of athletes arising at the attention level or at level of saccadic motor preparation.